Juridical Review Consumer Legal Against Labeling Of Food Products Based On Law No. 8 Year 1999 - Martina Lestari Ritonga (Institute Of computer Science (IOCS), 2021)
Consumer protection is in line with the development of the world economy. The rapid development of the world economy, especially in the trade sector, produces various types and variations of each type of goods and/or services that can be consumed. For consumers, information about goods and/or services is a basic need, before they use sources of funds to conduct consumer transactions with these goods and/or services. The right to correct information is one of the rights of consumers as regulated in Article 4 of Law no. 8 of 1999 concerning Consumer Protection. One source of the correct information is the label. In article 1 paragraph (3) of PP no. 69 of 1999 concerning Food Labels and Advertisements defines that what is meant by Food Labels is